下顎骨の骨延長が有用であった顔面多発骨折後変形治癒の1例 - 平井, 雄三; 山本, 信祐; 谷池, 直樹; 高地, いづみ; 竹信, 俊彦; 前田, 圭吾 (口腔顎顔面外傷 : 日本口腔顎顔面外傷学会誌, 2018)
Panfacial fracture is frequently associated with soft-tissue injuries and loss of bony structures that can lead to severe post-traumatic deformities and dysfunctions. Fractures malunite and soft tissues shrink if appropriate treatment is not provided soon after injury, making treatment extremely difficult. We report a case of facial malunion following delayed treatment for panfacial fracture successfully treated by mandibular distraction osteogenesis. In a traffic accident, a 65-year-old man suffered bilateral orbital floor, Le Fort Ⅰ/Ⅱ, and mandibular symphyseal fractures. The orbital floor and mandible were openly reduced and internally fixed at another hospital; other fractures in this region were conservatively managed. However, the treatment was inappropriate and three months later he was referred to our hospital because of severe malocclusion and mouth-opening limitation. Clinical examination showed a narrowed mandibular dental arch and crossbite on the right molars. Computed tomography revealed that the mandible was fixed inappropriately at the symphyseal region and bone healing in the right mandible was deviated to the lingual side. We performed mandibular midline distraction using a custom-made tooth-borne distractor （first stage） and Le Fort Ⅰ osteotomy （second stage）. The postoperative course was uneventful, and the patient regained stable occlusion and satisfactory mouth opening.